A molecular imprinted SPR biosensor for sensitive determination of citrinin in red yeast rice. (1st October 2015) - Atar, Necip; Eren, Tanju; Yola, Mehmet Lütfi
Highlights: Citrinin-imprinted SPR biosensor is developed for the sensitive detection of citrinin. Citrinin-imprinted (p(HEMA–MAGA)) film is characterized by several methods. Citrinin-imprinted SPR biosensor is sensitive and selective in analysis of mycotoxin. Citrinin-imprinted SPR biosensor offers the important advantages in food analysis. Citrinin-imprinted SPR biosensor is preferred to the other methods in food analysis. Abstract: A novel and sensitive molecular imprinted surface plasmon resonance (SPR) biosensor was developed for selective determination of citrinin (CIT) in red yeast rice. Firstly, the gold surface of SPR chip was modified with allyl mercaptane. Then, CIT-imprinted poly(2-hydroxyethyl methacrylate–methacryloylamidoglutamic acid) (p(HEMA–MAGA)) film was generated on the gold surface modified with allyl mercaptane. The unmodified and imprinted surfaces were characterized by Fourier transform infrared (FTIR) spectroscopy, atomic force microscopy (AFM) and contact angle measurements. The linearity range and the detection limit were obtained as 0.005–1.0 ng/mL and 0.0017 ng/mL, respectively. The SPR biosensor was applied to determination of CIT in red yeast rice sample.